Predictors and development patterns of approximal caries: a retrospective cross-sectional radiographic assessment - Fatma Yilmaz (BMC Oral Health)
Abstract Background The varied presentation of approximal caries in clinical practice complicates their prediction. This retrospective cross-sectional radiographic study aimed to evaluate the effects of adjacent surface status, age, sex, tooth type and dental arch on approximal caries as predictors. It was also aimed to evaluate the development patterns of approximal caries on adjacent surfaces facing each other. Methods The radiographic database of Faculty of Dentistry at Mugla Sitki Kocman University from 2019 to 2023 was used for this study. Of a total of 456 patients (aged 18–65, 196 men, 260 women), 752 carious and 337 non-carious approximal areas obtained from standart bitewing and periapical radiographs were included. To evaluate the predictors of approximal caries adjacent surface status (as carious, restored, missing or intact), age, sex, type (as anterior, canine, premolar or molar) and dental arch (as upper/lower-rigt/left jaw) of the approximal carious teeth were recorded. To assess the development patterns of approximal caries, carious surface and its adjacent surface were evaluated in pairwise and categorized as follows: “carious-carious, carious-restored, carious-missing, carious-intact”. On the other hand non-carious approximal areas were categorized as “intact-restored, intact-missing, intact-intact”. Lesion depth (E1, D2, D1, D2 or D3) was also recorded and associated with restoration type (amalgam, composite or crown) and adjacent surface status. The Pearson chi-square and Kappa statistic tests were used to examine the relationships between categorical variables (p < 0.05). Results The approximal caries incidance were higher in the group aged 18–39 years, men, upper right dental arch, and anterior–canine, and posterior approximal surfaces than others (p < 0.001). The caries-intact category was remarkably in high incidance. The depth of caries lesions was significantly influenced by the adjacent surface status, but not by type of restoration. It was found that D3 caries were the least frequently observed in carious-intact category while E1 and E2 caries were found more frequent in carious-carious category (p < 0.001). Conclusions Overall, these findings highlight the importance of considering a combination of demographic and dental factors in predicting, understanding and preventing approximal caries formation.